Similarities between Muslims and infidels in learning punishment comparative analysis - Husni, Ahmad Muhammad; Muhammad Husni, Amin (Zes Rokman Resources, 2025)
Islam emphasizes justice in carrying out and carrying out a punishment. Every criminal who com-mits a crime should be given a proper punishment according to the rules and guidelines set by the shara'. Punishment in Islam is not intended to take revenge and oppress the offender, but the pun-ishment is for the good of the criminals themselves and at the same time to protect the community. In the implementation of punishment, the principle of equality is the main basis without distinguish-ing between individual Muslims and non-Muslims. However, the principle of equality in punish-ment must be appropriate and not oppress criminals. Therefore, the researcher wants to study whether there are similarities and differences of opinion among scholars regarding the punishment between Muslims and infidels in hudud, qisas and takzir punishments. This study is a qualitative study, namely by studying books that discuss the punishments imposed on Muslims and infidels. As a result of this study, the researchers found that not all the punishments imposed on the infidels have similarities with Muslims. However, there is also an opinion that the infidels receive the same punishment as the Muslims. In addition, there are also punishments that are only specific to Mus-lims such as hudud punishment, while infidels are exempt from hudud punishment and the judge can choose to dismiss the case to a public court or impose hudud punishment also on infidels who commit offences under hudud punishment. Takzir punishment has many similarities because it is based on judges and the federal constitution. A person who believes in Allah s.w.t must accept the commands set by Allah as written in the Quran and hadiths. A constitution that does not challenge and challenges the integrity of Islam and the sanctity of Allah's law and does not deviate from the Islamic Aqidah and is also well thought of by Muslims must be accepted and appreciated as a valid constitution in terms of shara' law. Muslims and non-Muslims living in Islamic countries must obey what Islam has outlined so that the people can live in peace and harmony. In addition, the community can also live their lives without any feelings of fear and phobia if the community can follow and respect everything that Islam has taught